ANALISA PENGARUH METODE PELAKSANAAN PROYEK UNTUK EFISIENSI WAKTU DAN BIAYA PEKERJAAN GEDUNG BERTINGKAT DI KOTA PONTIANAK - Zainuddin, -; M.Nuh, Syafaruddin; Indrayadi, M. (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
The construction of multi-storey buildings in the city of Pontianak is very rapid, with the level of management difficulties and difficulties in implementing high-rise buildings. The longer the duration of time needed will affect the cost of completing the project. Because it requires an implementation method, which can support and consider the costs incurred in the implementation of the work. In addition, sharpening priorities is expected to increase efficiency and project management activities. All of that is to achieve the goal of a multi-storey building project that suits your needs. Different implementation methods in a building. must be followed by a good and appropriate project implementation. Good technical management and implementation can reduce the risk of multi-storey building construction projects and the delay becomes small. This will reduce the development of project costs, and ultimately will provide a distinct advantage for contractors. Analysis of the data used includes the implementation method in the construction of one building with two different implementation methods. The first method is casting 9th and 10th floors using a concrete pump and ready mix with truck concrete. Furthermore, the second implementation method uses the elevator machine and concrete mixer (Molen). The results obtained at the time efficiency value, because the implementation process is fast, the first method is the best solution, because in terms of cost is not much different from the second implementation method. Method one has a low cost of implementation, but the implementation time is not efficient.Keywords              : Analysis method, time and cost efficiency, good execution method